Electromagnetic field theory & transmission lines - Acharyya, Parimal (Aryan pub, 2017)
Electromagnetic field theory & transmission lines / Acharyya, Parimal. -- Kolkata: Aryan pub., 2017 539.2 Ac176 Rev. ed No. of Copies : 1